2007
DOI: 10.1038/nature06452
|View full text |Cite
|
Sign up to set email alerts
|

RNA-mediated epigenetic programming of a genome-rearrangement pathway

Abstract: Genome-wide DNA rearrangements occur in many eukaryotes but are most exaggerated in ciliates, making them ideal model systems for epigenetic phenomena. During development of the somatic macronucleus, Oxytricha trifallax destroys 95% of its germ line, severely fragmenting its chromosomes, and then unscrambles hundreds of thousands of remaining fragments by permutation or inversion. Here we demonstrate that DNA or RNA templates can orchestrate these genome rearrangements in Oxytricha, supporting an epigenetic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
339
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(351 citation statements)
references
References 35 publications
9
339
1
Order By: Relevance
“…The second way in which RNAs can affect cell heredity is by guiding, targeting, and assisting in transmitting variations in chromatin structure that are reconstructed and reproduced in daughter cells through the chromatin-marking EIS (Matzke and Birchler 2005;Ekwall 2007;Huettel et al 2007). The third way is by targeting DNA base sequences and guiding changes in them that are then replicated by DNA polymerases (Meyer and Chalker 2007;Nowacki et al 2008). Heritable variations can be generated and perpetuated through all three routes of RNA-mediated heredity, and the formation of a particular dsRNA may be affected by local conditions and may be developmentally regulated.…”
Section: Mechanisms Of Cellular Epigeneticmentioning
confidence: 99%
See 1 more Smart Citation
“…The second way in which RNAs can affect cell heredity is by guiding, targeting, and assisting in transmitting variations in chromatin structure that are reconstructed and reproduced in daughter cells through the chromatin-marking EIS (Matzke and Birchler 2005;Ekwall 2007;Huettel et al 2007). The third way is by targeting DNA base sequences and guiding changes in them that are then replicated by DNA polymerases (Meyer and Chalker 2007;Nowacki et al 2008). Heritable variations can be generated and perpetuated through all three routes of RNA-mediated heredity, and the formation of a particular dsRNA may be affected by local conditions and may be developmentally regulated.…”
Section: Mechanisms Of Cellular Epigeneticmentioning
confidence: 99%
“…Silencing may occur through any of the following mechanisms: (i) the siRNA is loaded onto an enzyme complex that interferes with the transcription or translation of mRNAs with a homologous se-quence (Cullen 2004;Meister and Tuschl 2004); (ii) the siRNA is loaded onto an enzyme complex that targets chromatin regions with DNA that is homologous to the siRNA, and alters chromatin into a silent state (Matzke and Birchler 2005;Ekwall 2007;Huettel et al 2007); or (iii) the siRNA is loaded onto an enzymatic complex that degrades and/or excises the DNA sequences complementary to the siRNAs. The latter processes of RNA-regulated DNA rearrangement are being intensely studied in ciliates (Meyer and Chalker 2007;Nowacki et al 2008).…”
Section: Mechanisms Of Cellular Epigeneticmentioning
confidence: 99%
“…Nevertheless, such a connection is not unprecedented. At least in some lower organisms, such as various species of ciliates, RNA has been demonstrated to serve as a guide or template for DNA rearrangement ( 23,24 ).…”
Section: Research Articlementioning
confidence: 99%
“…Our previous work revealed that noncoding template RNAs that originate from the parental macronucleus guide a highly elaborate process of DNA deletion, unscrambling, and assembly to form the macronuclear genome (32). Disruption of specific RNA templates disables rearrangement of the corresponding gene, and injection of artificial templates reprograms the DNA rearrangement pathway.…”
mentioning
confidence: 99%